Ethosuximide, valproic acid, and lamotrigine in childhood absence epilepsy: Initial monotherapy outcomes at 12 months. Issue 1 (21st November 2012) - Glauser, Tracy A.; Cnaan, Avital; Shinnar, Shlomo; Hirtz, Deborah G.; Dlugos, Dennis; Masur, David; Clark, Peggy O.; Adamson, Peter C.; for the Childhood Absence Epilepsy Study Team
Summary Purpose: Determine the optimal initial monotherapy for children with newly diagnosed childhood absence epilepsy (CAE) based on 12 months of double‐blind therapy. Methods: A double‐blind, randomized controlled clinical trial compared the efficacy, tolerability, and neuropsychological effects of ethosuximide, valproic acid, and lamotrigine in children with newly diagnosed CAE. Study medications were titrated to clinical response, and subjects remained in the trial unless they reached a treatment failure criterion. Maximal target doses were ethosuximide 60 mg/kg/day or 2, 000 mg/day, valproic acid 60 mg/kg/day or 3, 000 mg/day, and lamotrigine 12 mg/kg/day or 600 mg/day. Original primary outcome was at 16–20 weeks and included a video–electroencephalography (EEG) assessment. For this report, the main effectiveness outcome was the freedom from failure rate 12 months after randomization and included a video‐EEG assessment; differential drug effects were determined by pairwise comparisons. The main cognitive outcome was the percentage of subjects experiencing attentional dysfunction at the month 12 visit. Key Findings: A total of 453 children were enrolled and randomized; 7 were deemed ineligible and 446 subjects comprised the overall efficacy cohort. There were no demographic differences between the three cohorts. By 12 months after starting therapy, only 37% of all enrolled subjects were free from treatment failure on their first medication. At the month 12 visit, the freedom‐from‐failure rates for ethosuximide and valproic acid were similar (45% and 44%, respectively; odds ratio [OR]with valproic acid vs. ethosuximide 0.94; 95% confidence interval [CI] 0.58–1.52; p = 0.82) and were higher than the rate for lamotrigine (21%; OR with ethosuximide vs. lamotrigine 3.08; 95% CI 1.81–5.33; OR with valproic acid vs. lamotrigine 2.88; 95% CI 1.68–5.02; p < 0.001 for both comparisons). The frequency of treatment failures due to lack of seizure control (p < 0.001) and intolerable adverse events (p < 0.037) was significantly different among the treatment groups. Almost two thirds of the 125 subjects with treatment failure due to lack of seizure control were in the lamotrigine cohort. The largest subgroup (42%) of the 115 subjects discontinuing due to adverse events was in the valproic acid group. The previously reported higher rate of attentional dysfunction seen at 16–20 weeks in the valproic acid group compared with the ethosuximide or lamotrigine groups persisted at 12 months (p < 0.01). Significance: As initial monotherapy, the superior effectiveness of ethosuximide and valproic acid compared to lamotrigine in controlling seizures without intolerable adverse events noted at 16–20 weeks persisted at 12 months. The valproic acid cohort experienced a higher rate of adverse events leading to drug discontinuation as well as significant negative effects on attentional measures that were not seen in the ethosuximide cohort. These 12‐month outcome data coupled with the study's prespecified decision‐making algorithm indicate that ethosuximide is the optimal initial empirical monotherapy for CAE. This is the first randomized controlled trial meeting International League Against Epilepsy (ILAE) criteria for class I evidence for CAE (or for any type of generalized seizure in adults or children). (NCT00088452.)